Effect of depression and suicidal behavior on neuropeptide Y (NPY) and its receptors in the adult human brain: A postmortem study - Sharma, Anuradha; Ren, Xinguo; Zhang, Hui; Pandey, Ghanshyam N. (Progress in neuro-psychopharmacology & biological psychiatry, 2022)
Neuropeptides are small proteinaceous molecules (3–100 amino acids) that are secreted by neurons and act on both neuronal and non-neuronal cells. Neuropeptide Y (NPY), a highly conserved and expressed neuropeptide in the central nervous system of mammals, plays a major role in stress response and resilience. Increasing evidence suggests that NPY and its receptors are altered in depression and suicide, pointing to their antidepressant-like nature. The objective of this study was to examine the role of NPY system in depression and suicidal behavior. Expression of NPY and its four receptors, NPY1R, NPY2R, NPY4R, and NPY5R was studied at the transcriptional and translational levels in the prefrontal cortex (PFC) and hippocampus regions of the postmortem brain of normal control (NC) (n = 24) and depressed suicide (DS) (n = 24) subjects. We observed a significant decrease in NPY mRNA and upregulation in NPY1R and NPY2R mRNA in both brain regions of DS subjects compared with NC subjects. We also observed a significant decrease in NPY protein expression in the PFC of subjects with DS. This study provides the first detailed evidence of alterations in the NPY system and the associated stress response in depression and suicidal behavior in humans. The outcomes of this study could be applied in the development of novel NPY system-targeted approaches for the treatment of depression. •Neuropeptide Y (NPY) plays a major role in stress response and may have antidepressant-like effect.•Abnormalities of NPY and its receptors may be present in depression and suicide.•NPY mRNA and protein expression was decreased in postmortem brain of depressed suicide subjects.•mRNA expression of NPY1R and NPY2R was increased in postmortem brain of depressed suicide subjects.•Our results show NPY abnormalities in postmortem brain of depressed suicide subjects.